Fabrication and Characterization of Copper Doped Zinc Oxide on p-type and ntype Gallium Nitride by Sputtering - Yusof, Ahmad Sauffi; Hassan, Zainuriah; Zainal, Norzaini (2016)
Zinc oxide (ZnO) is a wide band gap semiconductor (3.3 7ev) with promising appli cations in optoelectroni c devices and flat panel display. Copper (Cu) doping changes the properti es of ZnO. Pure and Cu doped ZnO (CZO) were deposited on p-type and 11-type ga llium nitride (GaN) using radio fi·equency (RF) magnetron sputtering of Cu!ZnO alloy target with ratio I 0/90 at room temperature. The effect of different deposition thickness of the thin film on the crysta l structure, surface morphology and surface roughnesswere investigated intensively using X-ray diffraction (XRD), field em ission scanning electron microscopy (FE-SEM), energy dispersive X-ray spectroscopy (EDX) andatomic force microscopy (AFM)respectively. Results indicate th at the films with hexago nal wurtzite structure and preferential c ax is orientation were fabricated. Crystalli zation of thin film is dependent on the deposition thickness. As the thickness of the film increases, the grain size increases and surface roughness decreases.